Polymorphisms of Growth Hormone Gene Exon 1 and their Associations with Body Weight in Pitalah and Kumbang Janti Ducks - Yurnalis,; Husmaini,; Sabrina, (International Journal of Poultry Science, 2017)
Objective: The objective of this study was to determine Growth Hormone (GH) gene polymorphisms and their association with productive traits, including body weight, at ages 1, 2, 3, 4, 5, 6, 7 and 8 weeks. Methodology: Polymorphisms in exon 1 of the GH gene were evaluated in two duck populations in West Sumatra Province Indonesia (Pitalah and Kumbang Janti ducks). For this purpose, blood samples were collected and DNA samples were extracted using the Promega Wizard® Genomic DNA Purification Kit. For this purpose, a total 225 ducks blood samples were collected from 145 male and 80 female ducks. Genetic polymorphisms were determined with the Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) method using the Eco721 restriction enzyme and agarose gel electrophoresis. Direct sequencing of some samples was used to confirm the results. Results: Two alleles (GHG and GHA) and three genotypes (GH/GG, GH/GA and GH/AA) were found in the studied duck samples at locus GH/Eco721. In both groups of ducks, the dominant allele was GHG. The most frequent genotype in the examined ducks was GH/GA. Three genotypes were observed in the Pitalah ducks, whereas two genotypes (GH/GA and GH/GG) were identified in the Kumbang Janti ducks and in the males. Pitalah ducks with the GH/GA genotype were characterized by a higher (p